When is a monotone function cyclically monotone?. Issue 3 (26th July 2021) - Kushnir, Alexey I.; Lokutsievskiy, Lev V.
Abstract : We provide sufficient conditions for a monotone function with a finite set of outcomes to be cyclically monotone. Using these conditions, we show that any monotone function defined on the domain of gross substitutes is cyclically monotone. The result also extends to the domain of generalized gross substitutes and complements.